La sincérité des sentiments et des mots. Les logiques essentialisantes d’une économie morale occidentale des homosexualités masculines au Maroc - Marien Gouyon (L’Année du Maghreb)
This article proposes to approach elements defining the moral economies that build the plurality of homosexual identities today. The analysis of the social relations between Moroccan and French homosexuals makes it possible to understand that the imperative of sincerity carries specific values under the guise of a universal definition of homosexual identities. The ethnographic survey identifies, at the heart of the transformation of social relationships into inter-ethnic relations and racializing processes, the affirmation of love feeling as a value.